Pengaruh Perputaran Persediaan dan Penjualan Terhadap Profitabilitas PT Sumber Alfaria Trijaya Tbk Kota Batam - Gulo, Yahadi; Tipa, Handra (SCIENTIA JOURNAL, 2024)
IIncreases in inventory turnover and sales growth are not always followed by increases in profitability at PT. Sumber Alfaria Trijaya, Tbk Batam. Testing and analyzing inventory turnover and sales simultaneously influence PT's profitability. Sumber Alfaria Trijaya Batam. The design of this research is research using a quantitative approach. In this research, the population used by researchers is PT. SUMBER ALFARIA TRIJAYA TBK Batam City in 2018-2022. So the population in this study consists of 63 Alfamart outlets in Batam City. Inventory turnover has a significant positive effect on profitability, because the higher the level of inventory turnover, the higher the costs that can be reduced so that the greater the ROA a company obtains. Sales have a significant positive effect on profitability, where when the amount of sales growth increases, ROA will also increase. Inventory turnover and sales simultaneously have a significant effect on profitability, so that increasing inventory turnover and sales will increase the company's ROA. Companies must review the level of the inventory it has and the company must improve its techniques for managing and controlling inventory, so that it does not become empty or excessive so that it will not incur maintenance costs and ordering costs, losses and profits can be increased.Keywords: inventory turnover (IT),sales growts and profitability (ROA)